1980
DOI: 10.1038/bjc.1980.31
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin-like material extracted from squamous carcinomas of the head and neck

Abstract: Summary.-Tumour-associated prostaglandin-like material, assessed by bioassay, has been examined in 37 patients with primary and metastatic squamous carcinomas of the head and neck, previously treated by radiotherapy and chemotherapy followed by radical surgery. High amounts of prostaglandin-like material were extracted from tumours excised within 3 months of radiotherapy and chemotherapy. These amounts correlated with necrosis, inflammation and fibrosis, but not with tumour site, size or degree of differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…These observations indicate that PGs are likely to be involved, and the findings are compatible with results from fresh squamous carcinomas of the head and neck (Bennett et al, 1980). The evidence that PGs are released in vitro and induce bone resorption is, however, still indirect, and work is in progress to separate and characterize these indomethacin-sensitive factors.…”
Section: In Vitro Osteolysis By Fresh Squamouis Carcinomasupporting
confidence: 77%
See 1 more Smart Citation
“…These observations indicate that PGs are likely to be involved, and the findings are compatible with results from fresh squamous carcinomas of the head and neck (Bennett et al, 1980). The evidence that PGs are released in vitro and induce bone resorption is, however, still indirect, and work is in progress to separate and characterize these indomethacin-sensitive factors.…”
Section: In Vitro Osteolysis By Fresh Squamouis Carcinomasupporting
confidence: 77%
“…The underlying mechanisms of the osteolytic process are not clear, though preliminary investigations have shown that freshly excised squamous carcinomas of the head and neck contain extractable prostaglandin (PG)-like materials (Bennett et al, 1980) which, inter alia, activate osteoclasts. The extracted material is predominantly of the PGE type, and appears to be produced in the immediate vicinity of the tumour-probably from both carcinoma cells and host (stromal) (2.5 jg/ml fungizone, 100 jig/ml kanamycin), fresh ascorbic acid (150 jg/ml) and Lglutamine (200 jug/ml).…”
mentioning
confidence: 99%
“…Since fever in this disease has been attributed to secretion of prostaglandins by tumour tissue, a role for these agents in red-cell deformability may be indicated. Several very recent studies also report increased production of prostaglandins in other solid tumours, both in experimental animals and in man (Bennett et al, 1980;Droller et al, 1979;Fiedler et al, 1979;Trevisani et al, 1980). Even though stageing is a crude way of deciding tumour burden and the patient material is too small to be analysed in detail, it seems that Group A patients, apart from anaemia, had clinically slightly more advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary bioassays indicated that these tumours contained increased amounts of "prostaglandin-like materials" (Bennett et al, 1980) and subsequent work confirmed that a mixture of indomethacin-sensitive prostaglandins (mainly E2) and non-prostaglandin osteolysins was released by squamous carcinomas and their associated stroma (Tsao et al, 1981;1983, submitted for publication). Xenografts have been grown from some of our established squamous carcinoma cell lines (Easty et al, 1981a, b) and this report describes the effects of such xenografts on plasma calcium levels in the host and their osteolytic activity in vitro.…”
mentioning
confidence: 92%